(3TQM GdedNUs - (3UdGM GdOjf, bGVj RGOI, ehSi Hf eMeO Hf eMehO, J fMh (B840(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj LYd GdTeS VjGA hGdbeQ fhQG(B...(3hHYO Efg aj ReGffG gPG bO GfOQSJ eOGQS GdYdhe GdMbjbjI(B...s
(3BNQgG (B:s
(3WQjb CNQi CSgd ef GdChd fCNP jhe chf GdTeS aj CMO GdLRFjf GdSGHbjf dcd NeSI YTQI OQLI ef GdJaGhJ Hjf GdWhdjf SGYI(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B7(3,U(B328s
(3cTa GdXfhf(B:(3L(B2(3,U(B1819s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3Gdadc hGdJfLje hGdejbGJs